Constructing an Urban Drug Ecology in 1970s Canada - Marquis, Greg (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2013)
In 1970, youthful researchers carried out participant-observer studies of the drug scene in Vancouver, Winnipeg, Toronto, Montreal, and Halifax. This ethnographic research, prepared for the federal Commission of Inquiry into the Non-Medical Use of Drugs (the LeDain Commission), was part of the commission’s extensive series of unpublished studies. The commission, which released an initial report in 1970, one on cannabis in 1972 and a final report in 1973, adopted a broad approach to the issue of drugs and society. This article examines the unpublished studies as examples of social science “intelligence gathering” on urban social problems. The reports discussed the local market in illegal drugs, its geographic patterns and organizational features, the demographic characteristics of drug sellers and consumers, the culture of the drug scene, and the attitudes of users. Unlike earlier sociological and anthropological studies that focused on prisoners and lower-class “junkies” or more recent studies that examine marginalized inner-city populations, the city studies reflected the era’s fixation on middle-class youth culture and the addiction-treatment sphere’s growing concern with amphetamine abuse.